Suitability of compensatory saltmarsh habitat for feeding and diet of multiple estuarine fish species. (5th November 2022) - Stamp, Thomas; West, Elizabeth; Colclough, Steve; Plenty, Shaun; Ciotti, Benjamin; Robbins, Tim; Sheehan, Emma
Abstract: Saltmarsh provides essential fish feeding and nursery habitat but has globally declined by 50%. We used a statistical block design to compare fish feeding activity within human‐engineered or "re‐aligned" saltmarsh to established saltmarsh. Linear and multivariate modelling highlighted that Thinlip Mullet ( Chelon ramada ) and European Bass ( Dicentrarchus labrax ) feeding rates were 16% and 31% lower within re‐aligned than established saltmarshes, whereas Gobies ( Pomatoschistus spp.) fed at the same rate as in both habitats. Analysis of European bass and Goby gut contents highlighted that important detritivorous prey species were up to 85.6% lower in re‐aligned sites. Lower vegetation density may have negatively affected the feeding ecologies of fishes within re‐aligned sites. However, due to the ecological value and potential for further improvement or habitat development, continued assessment of the beneficial effects of re‐aligned sites for fisheries and net gain perspectives is needed.